S15: Understanding Factors Affecting Participation in Adapted Physical Activity: Lifetime Engagement (Baltic Journal of Sport and Health Sciences, 2026)
Individuals with disabilities face substantial challenges in achieving adequate physical fitness and maintaining regular physical activity. These challenges are associated not only with functional limitations but also with environmental, social, and motivational barriers. This symposium integrates findings from studies conducted in Latvia, Finland, and Lithuania addressing the factors affecting participation in physical activity of individuals with various disabilities across different age groups.The first presentation will present findings from a state-funded project examining the effects of functional limitations on the physical performance of school-aged children with intellectual, visual, hearing, and physical disabilities in Latvia. Comparative results with typically developing peers will be discussed, focusing on the potential for implementing inclusive physical activity programmes. Emphasis will be placed on the use of standardised assessment tools to monitor changes in health and physical fitness over time. The findings underscore the importance of adapting physical education programmes to address diverse functional needs and to promote equitable, inclusive fitness opportunities for all children.The second study from Finland will present national-level findings on physical activity trends among adolescents with disabilities, based on repeated cross-sectional survey data. The concurrent decline in participation in organised sports has been observed, suggesting a shift towards more unstructured or self-directed physical activity. These patterns highlight the need for adaptive, accessible, and interest-driven physical activity opportunities that account for the heterogeneous needs and preferences of adolescents with disabilities. The findings emphasise the importance of developing inclusive strategies that extend beyond traditional sport settings to promote sustained engagement in physical activity.The third study from Lithuania will present the key barriers to physical activity among adults with physical disabilities. Notably, gender differences emerged, with women reporting limited support from sports centre staff and challenges in accessing adapted transportation. Additionally, social isolation was associated with reduced physical activity levels, underscoring the critical role of community and interpersonal support in facilitating engagement.Together this symposium will emphasise the need for comprehensive and inclusive strategies that promote physical activity among individuals with disabilities. Efforts must go beyond addressing functional limitations and also target environmental, institutional, and social barriers.